O Problema de transplante de rins: uma abordagem na computação evolucionária - Furtado, Raul Silveira de Araújo (2019)
This work addresses the problem of kidney transplantation, with priority in the care of organ receptor patients, proposes find it a resolution methodology for the problem based on operational research techniques. In this case, the main objective is to perform as many transplants as possible with the lowest surgical and mobility costs, taking into account the georeferenced positions of donors, receptors and hospitals, as well as surgical costs accredited hospitals to perform kidney transplant surgeries. The problem meets the characteristics imposed by the Unified Health System (SUS) of the Ministry of Health of the Federative Republic of Brazil. Thus, our work aims to reduce the waiting time of the queue of these patients who need a kidney transplant and give an optimized planning to perform this task by the competent organs. A review in the literature was made on the subject and a problem was found with similar characteristics of what we treated in this work, in this case the Kidney Ex-change Problem (KEP), but not with the approach presented here. It developed for the specific problem: a mathematical model; a set of instances; and a metaheuristic, based on genetic algorithm, applies it to solving the problem. The results of the application of metaheuristics were presented with very satisfactoryness.